Legal Protection for Victims of Domestic Violence - Herlina Novica Saragih; Tamaulina Br Sembiring (Ipso Jure, 2024)
Domestic violence remains a pervasive issue globally, often leaving victims without a sense of justice or adequate protection. In many cases, resolutions fail to address the needs of domestic violence victims, perpetuating their suffering and leaving them vulnerable to further harm. Recognizing the severity of this issue, the implementation of legal protections outlined in Law Number 23 of 2004 concerning the Elimination of Domestic Violence is crucial. The research method employed by the author utilizes a normative legal approach, focusing on legal norms within statutory regulations. By gathering primary and secondary legal materials, the author examines the problem of domestic violence and seeks to align findings with established legal principles. This methodological approach, supplemented by literature reviews, enables the author to conclude the unequal dynamics within marital relationships that perpetuate domestic violence. Legal protection for victims of domestic violence is paramount as all forms of violence, particularly within the home, constitute human rights violations. Victims endure physical, psychological, and sexual abuse, as well as neglect, resulting in profound suffering and loss. Ensuring the protection of victims' rights is imperative to deliver justice and alleviate their trauma. However, many victims hesitate to report domestic violence due to feelings of embarrassment or fear of further harm. This reluctance underscores the critical need for comprehensive legal protections that prioritize the safety and well-being of victims. By fostering an environment of support and empowerment, victims can feel more confident in seeking justice and breaking the cycle of abuse. In conclusion, addressing domestic violence requires a multifaceted approach that combines legal enforcement with social support systems. By upholding the principles outlined in Law Number 23 of 2004 and providing comprehensive protections for victims, society can work towards eradicating domestic violence and ensuring justice for all.